Von Hippel-Lindau (VHL) inactivation in sporadic clear cell renal cancer: associations with germline VHL polymorphisms and etiologic risk factors. - Lee E Moore; Michael L Nickerson; Paul Brennan; Jorge R Toro; Erich Jaeger; Jessica Rinsky; Summer S Han; David Zaridze; Vsevolod Matveev; Vladimir Janout; Hellena Kollarova; Vladimir Bencko; et al. (PLoS Genetics, 2011)
Renal tumor heterogeneity studies have utilized the von Hippel-Lindau VHL gene to classify disease into molecularly defined subtypes to examine associations with etiologic risk factors and prognosis. The aim of this study was to provide a comprehensive analysis of VHL inactivation in clear cell renal tumors (ccRCC) and to evaluate relationships between VHL inactivation subgroups with renal cancer risk factors and VHL germline single nucleotide polymorphisms (SNPs). VHL genetic and epigenetic inactivation was examined among 507 sporadic RCC/470 ccRCC cases using endonuclease scanning and using bisulfite treatment and Sanger sequencing across 11 CpG sites within the VHL promoter. Case-only multivariate analyses were conducted to identify associations between alteration subtypes and risk factors. VHL inactivation, either through sequence alterations or promoter methylation in tumor DNA, was observed among 86.6% of ccRCC cases. Germline VHL SNPs and a haplotype were associated with promoter hypermethylation in tumor tissue (OR = 6.10; 95% CI: 2.28-16.35, p = 3.76E-4, p-global = 8E-5). Risk of having genetic VHL inactivation was inversely associated with smoking due to a higher proportion of wild-type ccRCC tumors [former: OR = 0.70 (0.20-1.31) and current: OR = 0.56 (0.32-0.99); P-trend = 0.04]. Alteration prevalence did not differ by histopathologic characteristics or occupational exposure to trichloroethylene. ccRCC cases with particular VHL germline polymorphisms were more likely to have VHL inactivation through promoter hypermethylation than through sequence alterations in tumor DNA, suggesting that the presence of these SNPs may represent an example of facilitated epigenetic variation (an inherited propensity towards epigenetic variation) in renal tissue. A proportion of tumors from current smokers lacked VHL alterations and may represent a biologically distinct clinical entity from inactivated cases.